Multi-method sensory approach to describe the effect of microwave-assisted extraction and addition of stems on the mouthfeel sensations of Bonarda wines from Mendoza (Argentina) - Álvarez Gaona, Izmari Jasel (2022)
Fil: Álvarez Gaona, Izmari Jasel. Pontificia Universidad Católica Argentina. Facultad de Ingeniería y Ciencias Agrarias; Argentina